A Quantitative Real-Time RT-PCR Assay for the Detection of Venezuelan equine encephalitis virus Utilizing a Universal Alphavirus Control RNA. (29th November 2016) - Vina-Rodriguez, Ariel; Eiden, Martin; Keller, Markus; Hinrichs, Winfried; Groschup, Martin H.
Abstract : Venezuelan equine encephalitis virus (VEEV) is an Alphavirus from the family Togaviridae that causes epizootic outbreaks in equids and humans in Central and South America. So far, most studies use conventional reverse transcriptase PCR assays for the detection of the different VEEV subtypes. Here we describe the development of a TaqMan quantitative real-time reverse transcriptase PCR assay for the specific detection and quantitation of all VEEV subtypes which uses in parallel a universal equine encephalitis virus control RNA carrying target sequences of the three equine encephalitis viruses. The control RNA was used to generate standard curves for the calculation of copy numbers of viral genome of Eastern equine encephalitis virus (EEEV), Western equine encephalitis virus (WEEV), and VEEV. The new assay provides a reliable high-throughput method for the detection and quantitation of VEEV RNA in clinical and field samples and allows a rapid differentiation from potentially cocirculating EEEV and WEEV strains. The capability to detect all known VEEV variants was experimentally demonstrated and makes this assay suitable especially for the surveillance of VEEV.